2014
DOI: 10.1371/journal.pone.0086157
|View full text |Cite
|
Sign up to set email alerts
|

Pirate Stealth or Inattentional Blindness? The Effects of Target Relevance and Sustained Attention on Security Monitoring for Experienced and Naïve Operators

Abstract: Closed Circuit Television (CCTV) operators are responsible for maintaining security in various applied settings. However, research has largely ignored human factors that may contribute to CCTV operator error. One important source of error is inattentional blindness – the failure to detect unexpected but clearly visible stimuli when attending to a scene. We compared inattentional blindness rates for experienced (84 infantry personnel) and naïve (87 civilians) operators in a CCTV monitoring task. The task-releva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 38 publications
6
19
0
Order By: Relevance
“…When broken down by participants, approximately 45% (n = 17) of participants in the control condition indicated that they had noticed an unusual item or individual, other than the victims, in the hallway. This detection rate fits with existing literature that suggests about half of all participants would be expected to notice an unexpected stimulus when not under high cognitive load (e.g., Chabris et al, 2011;Liao & Chiang, 2016;Näsholm et al, 2014). However, when asked to provide details of what participants had seen in the video, only one participant indicated that they had noticed the scenario-relevant unexpected stimulus (i.e., the suitcase), while 69% (n = 11) noted that they saw something unusual about the victims or the shooter, 12.5% (n = 2) indicated seeing an unusual item that was not the suitcase, and 19% (n = 3) noted seeing other unusual or unexpected stimuli (e.g., a mannequin and identifying tags worn by volunteers in the video).…”
Section: Datasupporting
confidence: 90%
“…When broken down by participants, approximately 45% (n = 17) of participants in the control condition indicated that they had noticed an unusual item or individual, other than the victims, in the hallway. This detection rate fits with existing literature that suggests about half of all participants would be expected to notice an unexpected stimulus when not under high cognitive load (e.g., Chabris et al, 2011;Liao & Chiang, 2016;Näsholm et al, 2014). However, when asked to provide details of what participants had seen in the video, only one participant indicated that they had noticed the scenario-relevant unexpected stimulus (i.e., the suitcase), while 69% (n = 11) noted that they saw something unusual about the victims or the shooter, 12.5% (n = 2) indicated seeing an unusual item that was not the suitcase, and 19% (n = 3) noted seeing other unusual or unexpected stimuli (e.g., a mannequin and identifying tags worn by volunteers in the video).…”
Section: Datasupporting
confidence: 90%
“…Nowadays, many occupations require high levels of vigilance, for example, security personnel [10], employees tasked with monitoring surveillance cameras or baggage screening experts [11], driving vehicles [12], diagnostic medical screening [13], real classroom settings [14], and industrial and air traffic control [15][16][17]. The need to remain alert and situation-aware, and to detect infrequent but critical signals is crucial in a lot of job occupations: A vigilance failure in any of these domains could have dramatic impacts.…”
Section: Current Key Research Points On Vigilancementioning
confidence: 99%
“…Retaining attention above a constant level is of vital importance in many applications. Some examples of entities that need sustained vigilance include pilots in aircraft [1], drivers operating vehicles [2], security forces in defense systems [3], cyber intrusion detection [4], industrial process control settings [5], and real classroom settings [6].…”
Section: Introductionmentioning
confidence: 99%